Dynamical identification of controls for parabolic variational inequalities - Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
The reconstruction problems of the unknown parameters based on the available information is one of the fundamental problems in the field of optimal control. This paper presents a new method of the positional modelling of distributed controls for the system described by the parabolic variational inequalities.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka